Digital competency among the aged entrepreneurs under the silver economy with soft power in Thailand - Intraratat, Kamolrat; Lomchavakarn, Piyachat; Punnahitanond, Ratanasuda; Boonsawad, Panicha; Intaratat, Duangkamol (Edelweiss Applied Science and Technology, 2025)
The rise of the elderly in Thailand experiencing a significant demographic transformation resulted in a growing senior population to become a super-aged society by 2030. This affacted the demand for “silver economy in Thailand. The objectives are to study (1) the overview of digital competency among the aged entrepreneurs under the silver economy with soft power; and (2) the mechanism for digital competency empowerment among the aged entrepreneurs under the silver economy with soft power in Thailand. Mixed-research method was employed by quantitative (survey questionnaire) and qualitative (Focus group discussion and interview) with a total of 100 samples and 15 key informants involved: the government workers, the aged entrepreneurs, the private & industrial workers, the digital competency expertise, the elderly expertise, and the community leaders. Two main results reflected the objectives accordingly: 1) the overview of digital competency summarized from survey questionnaire found most of the positive factors as follow; 1.1) positive attitude toward digital competency even of their quite low educational background; 1.2) their positive practical existing skilled in digital competency : digital communication, digital media production, privacy, security, analytic thinking skills that can be well applied with their silver economy’s activities. 2) the mechanism for digital competency empowerment among the aged entrepreneurs found most urgent needs in more closed collaboration among all relevant sectors, starting from the lead government sector, private sector, and the local sectors to help expanding all kinds of empowerment activities. Deepen links by driving more inter-sectoral mechanism, resources sharing, regular consultation for internship, apprenticeship, on-site training, employment, market outlet and other schemes with equity, quality and sustainable practices.